Association between in-hospital guideline adherence and postdischarge major adverse outcomes of patients with acute coronary syndrome in Vietnam: a prospective cohort study. Issue 10 (5th October 2017) - Nguyen, Thang; Le, Khanh K; Cao, Hoang T K; Tran, Dao T T; Ho, Linh M; Thai, Trang N D; Pham, Hoa T K; Pham, Phong T; Nguyen, Thao H; Hak, Eelko; Pham, Tam T; Taxis, Katja
Abstract : Objective: We aimed to determine the association between physician adherence to prescribing guideline-recommended medications during hospitalisation and 6-month major adverse outcomes of patients with acute coronary syndrome in Vietnam. Design: Prospective cohort study. Setting: The study was carried out in two public hospitals in Vietnam between January and October 2015. Patients were followed for 6 months after discharge. Participants: Patients who survived during hospitalisation with a discharge diagnosis of acute coronary syndrome and who were eligible for receiving at least one of the four guideline-recommended medications. Exposures: Guideline adherence was defined as prescribing all guideline-recommended medications at both hospital admission and discharge for eligible patients. Medications were antiplatelet agents, beta-blockers, ACE inhibitors or angiotensin II receptor blockers and statins. Main outcome measure: Six-month major adverse outcomes were defined as all-cause mortality or hospital readmission due to cardiovascular causes occurring during 6 months after discharge. Cox regression models were used to estimate the association between guideline adherence and 6-month major adverse outcomes. Results: Overall, 512 patients were included. Of those, there were 242 patients (47.3%) in the guideline adherence group and 270 patients (52.3%) in the non-adherence group. The rate of 6-month major adverse outcomes was 30.5%. A 29% reduction in major adverse outcomes at 6 months after discharge was found for patients of the guideline adherence group compared with the non-adherence group (adjusted HR, 0.71; 95% CI, 0.51 to 0.98; p=0.039). Covariates significantly associated with the major adverse outcomes were percutaneous coronary intervention, prior heart failure and renal insufficiency. Conclusions: In-hospital guideline adherence was associated with a significant decrease in major adverse outcomes up to 6 months after discharge. It supports the need for improving adherence to guidelines in hospital practice in low-income and middle-income countries like Vietnam.